PENERAPAN TEKNOLOGI TEPAT GUNA ALAT PENABUR PUPUK UREA DI DESA MONTOR - Muttaqin, Saipullah Zainal; Safitri, Ratu Diana; Mardotilah, Nadia; Fahri, Muhammad Fathul; Deden, Deden (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service project was conducted in Tani Makmur Village, aiming to introduce and implement appropriate technology in the form of a simple fertilizer spreader. The program was initiated to address farmers' challenges, namely time and labor inefficiency, as well as health risks associated with manual fertilization methods that require a bent posture. In this activity, the KKN students not only conducted socialization sessions but also held a participatory workshop to build the fertilizer spreader with the community using locally available materials like PVC pipes. As a result, the farming community realized that the fertilization process could be more efficient, faster, and ergonomic. The fertilizer spreader proved to reduce physical fatigue, shorten working time, and ensure a more even distribution of fertilizer. This project successfully raised awareness about the importance of simple innovations and strengthened the collaboration between students and the community in solving local agricultural problems.